Temperature-Regulated Transcription in the Pathogenic Fungus Cryptococcus neoformans - Steen, Barbara R.; Lian, Tian; Zuyderduyn, Scott; MacDonald, William Kim; Marra, Marco; Jones, Steven J.M.; Kronstad, James W. (Genome Research, 2002)
The basidiomycete fungus Cryptococcus neoformans is an opportunistic pathogen of worldwide importance that causes meningitis, leading to death in immunocompromised individuals. Unlike many basidiomycete fungi, C. neoformans is thermotolerant, and its ability to grow at 37°C is considered to be a virulence factor. We used serial analysis of gene expression (SAGE) to characterize the transcriptomes of C. neoformans strains that represent two varieties with different polysaccharide capsule serotypes. These include a serotype D strain of the C. neoformans varietyneoformans and a serotype A strain of variety grubii. In this report, we describe the construction and characterization of SAGE libraries from each strain grown at 25°C and 37°C. The SAGE data reveal transcriptome differences between the two strains, even at this early stage of analysis, and identify sets of genes with higher transcript levels at 25°C or 37°C. Notably, growth at the lower temperature increased transcript levels for histone genes, indicating a general influence of temperature on chromatin structure. At 37°C, we noted elevated transcript levels for several genes encoding heat shock proteins and translation machinery. Some of these genes may play a role in temperature-regulated phenotypes in C. neoformans, such as the adaptation of the fungus to growth in the host and the dimorphic transition between budding and filamentous growth. Overall, this work provides the most comprehensive gene expression data available forC. neoformans; this information will be a critical resource both for gene discovery and genome annotation in this pathogen.[This paper is dedicated to the memory of Michael Smith, founding director of the Biotechnology Laboratory and the British Columbia Genome Sciences Centre. The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: Brendan Loftus, Claire Fraser, Richard Hyman, Eula Fung, Don Rowley, Ron Davis , Bruce A. Roe, Doris Kupfer, Jennifer Lewis, Sola Yu, Kent Buchanan, Dave Dyer, and Juneann Murphy.]